A protein pore with a single polymer chain tethered within the lumen - Howorka, S; Movileanu, L; Lu, X; Magnon, M; Cheley, S; Braha, O; Bayley, H (2000)
A transmembrane protein pore with a single 5000 Da poly(ethylene glycol) (PEG) molecule attached covalently within the channel lumen has been constructed from seven staphylococcal α-hemolysin subunits. The modified heptamer is stable and can be purified by electrophoresis in sodium dodecyl sulfate, without dissociation of the subunits. The properties of the modified pore were studied by single channel current recording. The PEG molecule reduces the mean conductance of the pore by 18%, as would be predicted from the effects of PEG on the conductivity of bulk electrolytes. The recordings also reveal a variety of low amplitude current fluctuations on a time scale of seconds, which are tentatively ascribed to the reorganization of the PEG molecule within the channel lumen and associated movements of the polypeptide chain. Another class of events, comprising uniform high-amplitude negative fluctuations in current with durations of milliseconds, is ascribed to motions of the PEG molecule into one of the channel entrances, thereby producing more extensive channel block. When instead a 3000 Da PEG is attached within the channel lumen, the single channel properties are changed in keeping with the lower mass of the polymer. For example, the high-amplitude fluctuations occur more frequently and are of shorter duration suggesting that the 3000 Da PEG is more mobile than the 5000 Da chain. With further development, the approach taken here should be useful for the indirect monitoring of polymer dynamics at the single molecule level. By using polymers that respond to analytes, it should also be possible to make biosensors from the covalently modified pores.